Vida PURA: An assessment of the fidelity of promotor-delivered screening and brief intervention to reduce unhealthy alcohol use among Latino day laborers. Issue 4 (2nd October 2018) - Serrano, Samantha E.; Serafini, Kelly; Eller, Nikki; Torres, Vanessa N.; Donovan, Dennis; Ornelas, India J.
ABSTRACT: We assessed the fidelity of promotores conducting screening and brief intervention (SBI) to reduce unhealthy alcohol use among Latino immigrant day laborers in the Vida PURA study. We reviewed 32 audio-recorded brief interventions to assess promotor adherence to the intervention protocol and to evaluate their motivational interviewing (MI) technique with the Motivational Interviewing Treatment Integrity (MITI) 4.2.1 tool. Promotores delivered three core intervention steps in 78% of recordings and achieved basic MI competence across all domains and proficiency in 50% of measures. Our results suggest that promotores can be trained to deliver SBI in community settings with fidelity.